LOCUST OF CONTROL, KEAHLIAN AUDITOR DAN KINERJA AUDITOR - Harlyn Lindon Siagian; Doli Silaban (Program Studi Magister Manajemen Universitas Advent Indonesia, 2021)
Auditors who work objectively and follow the code of ethics in the assignment of auditing financial statements will produce good performance by providing a fair opinion in accordance with accounting principles. This study, was to determine the effect of Locust of Control and Auditor Expertise on Auditor Performance. The sample for this study was auditors who work in public accounting firms spread across Jakarta and the number of samples is 41 auditors. The author uses a valid and reliable questionnaire as a research instrument which was distributed to auditors as respondents in this study via google form. The results of the study are that there was a significant influence between Locust of Control and Auditor Expertise on Auditor Performance, either partially or simultaneously.